Phosphine radical cation catalysis for Markovnikov hydroamination of unactivated alkenes - Das, Nirmal; Barsu, Nagaraju (Journal of Chemical Sciences, 2026)
Markovnikov-selective hydroamination of unactivated terminal alkenes has long remained a challenging transformation in C-N bond formation. Fan and co-workers1 addressed this using a metal-free phosphine photoredox system that operates via an unprecedented phosphine radical cation (P(IV)) mechanism, enabling alkene activation toward azole addition. This work highlights a powerful new strategy for C(sp3)-N bond construction beyond traditional transition-metal catalysis.Graphical abstractMetal-free phosphine photoredox catalysis enables Markovnikov-selective hydroamination of unactivated terminalalkenes via a novel phosphine radical cation mechanism, off ering a new strategy for C(sp3)-N bond formation.
Keywords: azoles; hydroamination; Markovnikov selectivity; Phosphine catalysis; photoredox; radical cation